From feudal colonization to agrarian capitalism in Mallorca: Peasant endurance under the rise and fall of large estates (1229–1900). (25th January 2018) - Tello, Enric; Jover, Gabriel; Murray, Ivan; Fullana, Onofre; Soto, Ricard
Abstract : The colonization of Mallorca gave rise to a late‐feudal agrarian society that evolved towards capitalism based on large estates owned by noblemen who hired large numbers of wage labourers from among smallholders living in agro‐towns, the dispossessed remnants of a formerly wealthier peasantry. These well‐off peasants originated from when the colonization frontier was open in the 13th and 14th centuries, but had been defeated when three peasant–plebeian revolts were crushed. Afterwards, Mallorca followed a latifundist transition towards agrarian capitalism similar to southern Italy or Spain, in sharp contrast with the middle‐peasant paths seen in Catalonia or Valencia. The land rent rose, while agricultural wages fell from 1659 to 1800. Peasant families could not survive, and had to supplement wages with the products of their own plots. This set a socio‐agroecological limit to growth in this agrarian class structure. The agrarian crisis at the end of the 19th century bankrupted the Mallorcan nobility. Bankers bought much of the land and sold it on as small allotments. This expanded the intensive cropping formerly limited to agro‐town belts, giving rise to a new "peasantization". Despite their subordination, Mallorcan peasants had survived and created complex agroecological landscapes endowed with a rich biocultural heritage.